(untitled) (Research, Society and Development, 2024)
Feline asthma is a disease that is prevalent in young or middle-aged cats, with the main clinical signs being dry cough, mouth breathing, expiratory dyspnea, wheezing, cyanosis, crackles and weight loss. However, current therapeutic approaches have proven to be ineffective in preventing or reversing all pathological aspects of feline asthma. In this way, the development of new treatments for feline asthma that prove to be safe and effective are of fundamental importance for veterinary medicine. Stem cell therapy is presented to the market as a promising therapeutic approach since it has been shown to be safe and effective in the treatment of several diseases that affect both large and small animals. Therefore, this study aims to analyze the safety and efficacy of the treatment of feline asthma through stem cell transplantation, which mainly aims to obtain a methodology that allows the improvement of the quality of cats.